2
$\begingroup$

From the Wikipedia page, the Meissel–Mertens constant $M$ is defined as the limit: $$M:=\lim_{n\to\infty}\left(\sum_{p\leq n}\frac{1}{p}-\log\log n\right).$$ Why is it equal to $\gamma+\sum_{p}\left(\log(1-\frac{1}{p})+\frac{1}{p}\right)$? where $\gamma$ is the Euler–Mascheroni constant defined by $$\gamma:=\lim_{n\to\infty}\left(\sum_{k=1}^n\frac{1}{k}-\log n\right).$$ I tried to prove this, but cannot work it out.

$\endgroup$
  • 1
    $\begingroup$ $\gamma$ is the $c_0$ coefficient of the Laurent series of $\zeta(s)$ around $s=1$. while $M$ is the $c_0$ coefficient of the Laurent series of $ P(s) = \sum_p p^{-s}$ (or of $ P(s) - \ln(s-1)$ or something like that, I'm not sure) around $s=1$. $\endgroup$ – reuns Apr 14 '16 at 15:05
  • 1
    $\begingroup$ the second formula says that $M = \gamma - \sum_p \sum_{\nu=2}^\infty \frac{1}{\nu p^{\nu}}$ hence it is also the $c_0$ coefficient of the Laurent of $\zeta(s) - \sum_{\nu=2}^\infty \frac{P(\nu s)}{\nu}$. use that $P(s) = \sum_{m=1}^\infty \frac{\mu(m)}{m} P(m s)$ hence $\zeta(s) - \sum_{\nu=2}^\infty \frac{P(\nu s)}{\nu} = \zeta(s) - \sum_{\nu=2}^\infty \frac{1}{\nu}\sum_{m=1}^\infty \frac{\mu(m)}{m} P(m \nu s) = \zeta(s) - \sum_{l=2}^\infty P(l s) \sum_{d | l, d \ne 1} \frac{\mu(d)}{d} \frac{1}{l/d} = ...$ $\endgroup$ – reuns Apr 14 '16 at 15:13
1
$\begingroup$

Suppose we have a Dirichlet series

$$F(s) = \sum_{n = 1}^{\infty} \frac{a_n}{n^s}$$

that converges for $\operatorname{Re} s > 0$, and for the partial sums of the coefficients series we have

$$A(x) := \sum_{n \leqslant x} a_n = \varphi(x) + L + R(x)$$

with a "nice" smooth function $\varphi$ and $R(x) \to 0$. We can then split the integral representation

$$F(s) = s\int_1^{\infty} \frac{A(x)}{x^{1+s}}\,dx$$

into (hopefully) easier to analyse parts, namely

$$F(s) = s\int_1^{\infty} \frac{\varphi(x)}{x^{1+s}}\,dx + L + s\int_1^{\infty} \frac{R(x)}{x^{1+s}}\,dx\,.$$

We note that the last term tends to $0$ as $s \to 0$ inside an angular sector $\lvert \arg s\rvert \leqslant \alpha < \frac{\pi}{2}$, and so the limiting behaviour of $F(s)$ is determined by the first term and $L$. For, given an arbitrary $\delta > 0$, there is an $y \in [1,\infty)$ such that $\lvert R(x)\rvert \leqslant \delta$ for $x \geqslant y$, and splitting the integral at $y$ we observe that

$$E(s) := \int_1^y \frac{R(x)}{x^{1+s}}\,dx$$

is an entire function of $s$ (here we need that $\varphi$ is also nice enough near $1$ since $R$ would reflect any ugliness of $\varphi$ there; but if it weren't, we'd need to modify $\varphi$ to be able to split anyway) and hence $s\cdot E(s) \to 0$ as $s \to 0$. The remaining part can be bounded

$$\Biggl\lvert s\int_y^{\infty} \frac{R(x)}{x^{1+s}}\,dx\Biggr\rvert \leqslant \delta \lvert s\rvert \int_y^{\infty} \frac{dx}{x^{1+\sigma}} = \delta \frac{\lvert s\rvert}{\sigma y^{\sigma}} \leqslant \delta \frac{\lvert s\rvert}{\sigma}$$

where $\sigma = \operatorname{Re} s > 0$. If $\lvert \arg s\rvert \leqslant \alpha < \frac{\pi}{2}$, the quantity $\frac{\lvert s\rvert}{\sigma}$ is bounded by $\frac{1}{\cos \alpha}$, and so

$$\limsup_{\substack{s \to 0 \\ \lvert \arg s\rvert \leqslant \alpha}} \: \Biggl\lvert s\int_1^{\infty} \frac{R(x)}{x^{1+s}}\,dx\Biggr\rvert \leqslant \frac{\delta}{\cos\alpha}\,.$$

Since $\delta$ was arbitrary,

$$\lim_{\substack{s \to 0 \\ \lvert \arg s\rvert \leqslant \alpha}} s\int_1^{\infty} \frac{R(x)}{x^{1+s}}\,dx = 0$$

follows.

For $\varphi(x) = \log \log x$, we can explicitly evaluate the first integral, and thus can interpret the limiting behaviour. To look at how the decomposition of $M$ arises, we let $a_n = \frac{1}{n}$ if $n$ is prime and $a_n = 0$ otherwise (in closed form, $a_n = \frac{\pi(n) - \pi(n-1)}{n}$). Then $F(s) = P(1+s)$ where $P$ is the prime zeta function. We temporarily restrict $s$ to positive real numbers, so that the following manipulations allow a more elementary justification. Then

\begin{align} s\int_1^{\infty} \frac{\log \log x}{x^{1+s}}\,dx &= s\int_0^{\infty} \frac{\log t}{e^{(1+s)t}}e^t\,dt \tag{$x = e^t$} \\ &= s\int_0^{\infty} (\log t) e^{-st}\,dt \\ &= \int_0^{\infty} (\log u - \log s)e^{-u}\,du \tag{$u = st$} \\ &= \int_0^{\infty} (\log u)u^{1-1}e^{-u}\,du - \log s \int_0^{\infty} u^{1-1}e^{-u}\,du \\ &= \Gamma'(1) - (\log s)\Gamma(1) \\ &= \log \frac{1}{s} - \gamma\,. \end{align}

By the identity theorem this holds for $\operatorname{Re} s > 0$, and we have found

$$P(1+s) = \log \frac{1}{s} + (M - \gamma) + s\int_1^{\infty} \frac{R(x)}{x^{1+s}}\,dx\,,$$

where the last term tends to $0$ as $s\to 0$ in an angular sector. Thus $\gamma$ comes from $\Gamma'(1)$, not (directly) from the Laurent expansion of $\zeta$ about $1$. It occurs naturally whenever we have a coefficient sequence such that $\lim \bigl(A(x) - \log \log x\bigr)$ exists. To understand $M - \gamma$, we can compare the prime zeta function to another function with a logarithmic singularity at $1$. Since $\zeta$ has a simple pole at $1$ and its logarithm is easy to handle due to the Euler product, this is a natural choice. Writing

$$\zeta(s) = \frac{1}{s-1} + c_0 + c_1(s-1) + \dotsc = \frac{1 + c_0(s-1) + \dotsc}{s-1} = \frac{G(s)}{s-1}$$

where $G$ is an entire function with $G(1) = 1$ which has no zeros in the half-plane $\operatorname{Re} s > 1$, we find

$$\log \zeta(s) = \log\frac{1}{s-1} + \log G(s)$$

for $\operatorname{Re} s > 1$, or, translating by $1$,

$$\log \zeta(1+s) = \log \frac{1}{s} + \log G(1+s)$$

for $\operatorname{Re} s > 0$, where $\log G(1+s)$ is holomorphic in the right half-plane and on a neighbourhood of $0$, and tends to $0$ as $s \to 0$. It follows that

$$M - \gamma = \lim_{\substack{s \to 0 \\ \lvert \arg s\rvert \leqslant \alpha}} \bigl(P(1+s) - \log \zeta(1+s)\bigr)\,.$$

But from the Euler product we obtain (using the principal branch of the logarithm for each factor)

$$\log \zeta(1+s) = - \sum_p \log \biggl(1 - \frac{1}{p^{1+s}}\biggr)$$

and hence

$$P(1+s) - \log \zeta(1+s) = \sum_p \frac{1}{p^{1+s}} + \sum_p \log \biggl(1 - \frac{1}{p^{1+s}}\biggr) = \sum_p \Biggl(\frac{1}{p^{1+s}} + \log \biggl(1 - \frac{1}{p^{1+s}}\biggr)\Biggr)\,.$$

A Taylor expansion of the logarithms on the right shows that the series converges (absolutely) for $\operatorname{Re} s > -\frac{1}{2}$, so

$$M-\gamma = \lim_{s\to 0} \bigl(P(1+s) - \log \zeta(1+s)\bigr) = \sum_p \Biggl(\frac{1}{p} + \log \biggl(1 - \frac{1}{p}\biggr)\Biggr)\,.$$

A faster converging series for $M - \gamma$ is

$$M - \gamma = \sum_{m = 2}^{\infty} \frac{\mu(m)\log \zeta(m)}{m}\,.$$

Note that the above assumes the existence of

$$\lim_{x \to \infty} \:\Biggl(\sum_{p \leqslant x} \frac{1}{p} - \log \log x\Biggr)\,.$$

To prove the existence, write

$$\sum_{p \leqslant x} \frac{1}{p^{1+\varepsilon}} = \log \zeta(1+\varepsilon) - \sum_{p > x} \frac{1}{p^{1+\varepsilon}} + \bigl(P(1+\varepsilon) - \log \zeta(1+\varepsilon)\bigr)$$

for $\varepsilon > 0$ and apply summation by parts to

$$\sum_{p > x} \frac{1}{p^{1+\varepsilon}} = \sum_{p > x} \frac{\log p}{p}\cdot \frac{1}{p^{\varepsilon}\log p}\,,$$

using Mertens' first theorem

$$\Biggl\lvert \sum_{p \leqslant x} \frac{\log p}{p} - \log x\Biggr\rvert \leqslant 2\,.$$

Then let $\varepsilon \to 0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.